Changes in antidepressant use in Australia: A nationwide analysis (2015–2021). (January 2023) - de Oliveira Costa, Juliana; Gillies, Malcolm B.; Schaffer, Andrea L.; Peiris, David; Zoega, Helga; Pearson, Sallie-Anne
Background: Depression and anxiety affect 4–14% of Australians every year; symptoms may have been exacerbated during the COVID-19 pandemic. We examined recent patterns of antidepressant use in Australia in the period 2015–2021, which includes the first year of the pandemic. Methods: We used national dispensing claims for people aged ⩾10 years to investigate annual trends in prevalent and new antidepressant use (no antidepressants dispensed in the year prior). We conducted stratified analyses by sex, age group and antidepressant class. We report outcomes from 2015 to 2019 and used time series analysis to quantify changes during the first year of the COVID-19 pandemic (March 2020–February 2021). Results: In 2019, the annual prevalence of antidepressant use was 170.4 per 1000 women and 101.8 per 1000 men, an increase of 7.0% and 9.2% from 2015, respectively. New antidepressant use also increased for both sexes (3.0% for women and 4.9% for men) and across most age groups, particularly among adolescents (aged 10–17 years; 46–57%). During the first year of the COVID-19 pandemic, we observed higher than expected prevalent use (+2.2%, 95% CI = [0.3%, 4.2%]) among females, corresponding to a predicted excess of 45, 217 (95% CI = [5, 819, 84, 614]) females dispensed antidepressants. The largest increases during the first year of the pandemic occurred among female adolescents for both prevalent (+11.7%, 95% CI = [4.1%, 20.5%]) and new antidepressant use (+15.6%, 95% CI = [8.5%, 23.7%]). Conclusion: Antidepressant use continues to increase in Australia overall and especially among young people. We found a differential impact of the COVID-19 pandemic in treated depression and anxiety, greater among females than males, and greater among young females than other age groups, suggesting an increased mental health burden in populations already on a trajectory of increased use of antidepressants prior to the pandemic. Reasons for these differences require further investigation.